The Effect of Good Corporate Governance on Company Value with Financial Performance as a Moderation Variable (Case Study of Insurance Companies Listed on the Indonesia Stock Exchange) - Ardhia Meianti; Imsar Imsar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
In Indonesia, service companies, especially insurance companies, are among the growing companies because they have a fairly good growth rate. Insurance companies are financial institution companies that collect funds in the form of premiums from the public. Therefore, the company’s premium income must be utilized, one of which is by going public, namely by issuing securities offerings in the form of shares in the capital market. This study aims to determine the effect of Good Corporate Governance (GCG) proxied by the Board of Commissioners, Independent Commissioners, and the Audit Committee on Company Value with Financial Performance as a Moderating Variable (Case Study of Insurance Companies Listed on the Indonesia Stock Exchange for the 2018-2022 Period). The population of this study is insurance companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This study uses secondary quantitative data methods and the terms of sample selection are 10 companies for 5 years with 50 samples. The method of data analysis in this study is purposive sampling and Moderate Regression Analysis (MRA) using SPSS 22.0. The results of this study indicate that Good Corporate Governance (GCG) before and after being moderated by financial performance simultaneously has a significant effect on firm value. This means that with an increase in the mechanism of Good Corporate Governance (GCG) and financial performance, investor confidence will emerge so that it can increase the value of the company.